Appraisal of the entrustable professional activities (EPAs) patient care provider domain by North Dakota pharmacists - Scott DM; Kelsch MP; Hanel M; Friesner DL (Centro de Investigaciones y Publicaciones Farmaceuticas, 2019)
Background: Entrustable Professional Activities (EPAs) are the latest addition to a list of professional competencies that pharmacy educational organizations support, and accreditation organizations require, for assessment by colleges and schools of pharmacy. Objective: The study's objective is to assess the use of Core EPAs in the patient care domain (by practice setting, position, and preceptor status) in contemporary pharmacy practice. Methods: This survey assessed the EPA activities of pharmacists practicing in North Dakota. The pharmacists were asked "how many times in the past 30 days have you delivered the following services in your practice setting?" Response options were: 0, 1, 2, 3, 4, and 5 or more times. Results: Of 990 potential respondents, 457 pharmacists (46.1%) returned a survey, and 107 (10.8%) answered every survey item in the patient care domain. Respondents reported that the highest rated activity items "Collect information to identify a patient's medication-related problems and health-related needs," and "Analyze information to determine the effects of medication therapy, identify medication-related problems, and prioritize health-related needs" were performed an average of 3.9 times per week (SD=1.8), and 3.8 times per week (SD=2.0), respectively. Both of these items, were reported for 70% of the respondents at 5 or more times per week. For these items, the highest reported practice setting was 'other' practice settings (e.g., long-term care, community health centers) followed by chains, hospitals, and independent pharmacies. By position, clinical pharmacists and preceptors reported the highest activity levels for most EPAs and supportive example tasks. Conclusions: This study provides empirical evidence suggesting (but not proving) that EPAs have potential as a means to assess outcomes in pharmacy education and practice. Our study sets the stage for future work that further refines and assesses core EPA activities and supportive example tasks to measure the impact of how this process relates to outcomes of care.